PELATIHAN PENGEMBANGAN MEDIA MATEMATIKA BAGI GURU SEKOLAH DASAR MARDI WALUYA SINDANGLAYA CIANJUR - Clara Ika Sari Budhayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2020)
Mathematical media is one of the keys to the success of achieving mathematics learning goals. Learning mathematics will be more effective when using mathematical media in the process. The use of mathematical media in the learning process is not just about attracting students' interest and attention, but the media is a bridge to explain abstract mathematical concepts. Mathematical media functions as concrete modeling of mathematical concepts. The average elementary school teacher Mardi Waluya, has an old paradigm in carrying out mathematics learning. Mathematics is taught starting from concepts, formulas, and then applied in story problems as a model of problems in everyday life. This way of learning makes students experience boredom and even does not like learning mathematics. The use of mathematical media in learning is still less varied. The use of mathematical media is usually only on certain concepts or material. The development of mathematical media is less done because the teacher does not know how the media was developed to explain a mathematical concept. Mathematics media development training conducted with PGSD, Unika Atma Jaya has greatly assisted teachers in developing ideas about mathematical media. The activities in the training aim to make the teacher understand the important things needed to develop mathematical media. Teachers are invited to experience how easy it is to learn mathematics by using mathematical media that has been prepared by the resource person. Every activity recognized by the teacher is able to inspire the teacher in developing mathematics media. Examples of how to make and use mathematical media provided are very helpful for teachers in creating mathematical media by utilizing simple materials and tools. But the teachers also hoped for further training, both related to the mathematics media and learning methodsABSTRAKMedia matematika merupakan salah satu kunci keberhasilan pencapaian tujuan pembelajaran matematika. Pembelajaran matematika akan lebih efektif apabila menggunakan media matematika dalam prosesnya. Penggunaan media matematika dalam proses pembelajaran bukanhanya sekedar menarik minat dan perhatian siswa, namun media menjadi jembatan untuk menjelaskan konsep matematika yang bersifat abstrak. Media matematika berfungsi sebagai pemodelan konkrit konsep matematika. Rata-rata guru SD Mardi Waluya, memiliki paradigma lama dalam melaksanakan pembelajaran matematika. Matematika diajarkan mulai dari konsep, rumus, dan kemudian diaplikasikan dalam soal cerita sebagai model masalah dalam kehidupan sehari-hari. Cara pembelajaran yang demikian membuat siswa mengalami kebosanan bahkan menjadi tidak suka belajar matematika. Penggunaan media matematika dalam pembelajaran masih kurang variatif. Penggunaan media matematika biasanya hanya pada konsep atau materi tertentu saja. Pengembangan media matematika kurang dilakukan karena guru tidak tahu bagaimana media dikembangkan untuk menjelaskan suatu konsep matematika. Pelatihan pengembangan media matematika yang dilakukan bersama PGSD, Unika Atma Jaya sangat membantu guru dalam mengembangkan ide-ide mengenai media matematika. Aktivitas-aktivitas dalam pelatihan bertujuan agar guru memahami hal-hal penting yang diperlukan untuk dapat mengembangkan media matematika. Guru di ajak untuk merasakan bagaimana mudahnya belajar matematika dengan menggunakan media matematika yang sudah disiapkan narasumber. Setiap aktivitas diakui oleh guru mampu menginspirasi guru dalam mengembangkan media matematika. Contoh-contoh bagaimana membuat dan menggunakan media matematika yang diberikan sangat membantu guru-guru dalam menciptakan media matematika dengan memanfaatkan bahan dan alat sederhana. Namun guru-guru juga berharap adanya pelatihan lebih lanjut, baik terkait dengan media matematika maupun metode pembelajarannya.